Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
{x=2,y=2
Step-by-step explanation:
Equation 1:
Multiply both sides of the equation by a coefficient
{ 4(2x-y)=2*4
-5x+4y=-2
Apply Multiplicative Distribution Law
{8x-4y=2*4,-5x+4y=-2
8x-4y+(-5x+4y)=8+(-2)
Remove parentheses
8x-4y-5x+4y=8-2
Cancel one variable
8x-5x=8-2
Combine like terms
3x=8-2
Calculate the sum or difference
3x=6
Divide both sides of the equation by the coefficient of the variable
x=6/3
Calculate the product or quotient
x=2
Equation two:
{-5+4y=-2, x=2
-5*2+4y=-2
Calculate the product or quotient
-10+4y =-2
Reduce the greatest common factor (GCF) on both sides of the equation
-5+2y=-1
Rearrange unknown terms to the left side of the equation
2y=-1+5
Calculate the sum or difference
2y=4
Divide both sides of the equation by the coefficient of the variable
y=4/2
y=2
Hope this helps!!
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.